Effects of Classroom Observation of Parents to the Performance of Pupils - Ceria, Emerson T. (Future Science / FSH-PH Publications, 2021)
The study aimed to determine the effects of classroom observation of parents to the performance of pupils in Pandayan Elementary School for the school year 2019-2020. A descriptive research method was utilized in this study. A research – made instrument for pre-test and post-test aligned with the given learning competencies in the K to 12 Curriculum Guide in Grades 4 -6 was designed and undergone validity and reliability examination by peer-experts. After the validation from other Principals, the Division Research Chairperson has approved the instrument. The researcher also carried out a dry run before the actual pre-test and post-test assessment to the respondents. The gathered data from the tests were recorded and analyzed using Microsoft Excel and SPSS. The findings showed that the post-test scores have increased after the classroom observation of parents. In conclusion, there was a significant difference on the academic performance of pupils in Mathematics before and after classroom observation of parents.